Tuning the stability of alkoxyisopropyl protection groups - Liang, Zehong; Koivikko, Henna; Oivanen, Mikko; Heinonen, Petri (Beilstein Journal of Organic Chemistry, 2019)
Five different 2-alkoxypropan-2-yl groups are introduced as acid-labile protecting groups for the 5’- and 3’-hydroxy groups of a 2’-deoxynucleoside. All studied protecting groups were readily introduced with good to excellent yields using the appropriate enol ether as a reagent and 0.5 to 1 mol % p-toluenesulfonic acid as a catalyst. The protected compounds could be purified by silica gel column chromatography without degradation. The compatibility of these protecting groups in parallel use with benzoyl and silyl groups was verified. The stabilities of the different alkoxy acetal protecting groups were compared by following the kinetics of their hydrolysis at 25.0 °C in buffered solutions through an HPLC method. In the pH range 4.94 to 6.82 the hydrolysis reactions are of first order in the hydronium ion. The rate of hydrolysis correlates with the electron-donating or electron-withdrawing ability of the corresponding alkoxy group. The studied 2-alkoxypropan-2-yl groups and the relative rate constants for their cleavage from the 5’-hydroxy group of 2’-deoxythymidine were: cyclohexyloxy (krel = 7.7), isopropoxy (7.4), methoxy (1), benzyloxy (0.6) and 2,2,2-trifluoroethyloxy (0.04). The attachment of the same groups to the 3’-hydroxy group are from 1.3 to 1.9-fold more stable. The most reactive of these acetone-based acetal groups are faster removed than a dimethoxytrityl group, and they are easier to cleave completely in solution. The structural variation allows steering of the stability and lipophilicity of the compounds in some range.
Keywords: acetal; hydrolysis; protecting groups

(untitled) - Liu, B.; Thayumanavan, S. (J. Am. Chem. Soc., 2017)

Greene’s Protective Groups in Organic Synthesis - Wuts, P. G. M.; Greene, T. W. (John Wiley & Sons, Inc., 2006)

(untitled) - Smrt, J. (Collect. Czech. Chem. Commun., 1968)

(untitled) - Reese, C. B.; Saffhill, R.; Sulston, J. E. (Tetrahedron, 1970)

(untitled) - Reese, C. B.; Saffhill, R.; Sulston, J. E. (J. Am. Chem. Soc., 1967)

(untitled) - Mukaiyama, T.; Ohshima, M.; Murakami, M. (Chem. Lett., 1984)

(untitled) - Molina, A. G.; Kungurtsev, V.; Virta, P.; Lönnberg, H. (Molecules, 2012)

(untitled) - Le Noble, W. J.; Crean, P. J. (J. Org. Chem., 1962)

(untitled) - Delville, M. M. E.; van Gool, J. J. F.; van Wijk, I. M.; van Hest, J. C. M.; Rutjes, F. P. J. T. (J. Flow Chem., 2012)

(untitled) - Palafox, M. A.; Iza, N.; de la Fuente, M.; Navarro, R. (J. Phys. Chem. B, 2009)

(untitled) - Wann, S. R.; Kreevoy, M. M. (J. Org. Chem., 1981)

(untitled) - Salomaa, P. (Ann. Acad. Sci. Fenn., Ser. A2, 1961)

(untitled) - Kreevoy, M. M.; Eliason, R. (J. Phys. Chem., 1968)

(untitled) - Salomaa, P.; Kankaanperä, A.; Lajunen, M. (Acta Chem. Scand., 1966)

(untitled) - Krotz, A. H.; McElroy, B.; Scozzari, A. N.; Cole, D. L.; Ravikumar, V. T. (Org. Process Res. Dev., 2003)

(untitled) - Russell, M. A.; Laws, A. P.; Atherton, J. H.; Page, M. I. (Org. Biomol. Chem., 2009)